Human error analysis to reduce production defects with Sherpa method and Heart method in PT XYZ - Puspitasari, Ayu; Safitri, Ginda; Efionita, Yolanda; Halim, Muhammad Irsyad (Journal of Sustainable Community Development, 2025)
This study aims to analyze Human Error to Reduce Defects in Production with the Sherpa Method and the Heart Method at PT XYZ. Sherpa method to identify errors and Heart method to calculate the probability of errors. The results of data processing show a total of 9 tasks and descriptions of errors where errors are divided into 2 types of errors classified based on Sherpa error modes, namely errors in implementation (action errors) as many as 7 errors, errors in checking (Checking errors) as many as 2 errors. The results of the calculation of the HEP value in the production process of automation goods. The probability of error in production with the heart method where the highest HEP value is 0.16. The production process of automation goods at PT XYZ which often occurs in the mounting process with the highest HEP value of 0.1856.